ANALISIS STR ATEGI PEMASARAN KERAJINAN UKIR KAYU NANGKA UNTUK MEMASARKAN PRODUK DI PASAR DOMESTIK PADA UKIR KAYU RADHA - Syafril syafar (Jurnal Teknik Industri Terintegrasi, 2020)
In the era of development, industrial competition will be increasingly fierce, competition of the cosmetic market will provide opportunities and threats for local companies, carving art is one of Indonesia's traditional arts that holds various values. This research was conducted at Radha wood carving located at Gmp3 Mustamindo. The method used is a SWOT analysis, SWOT analysis is one method for describing conditions and evaluating a project problem or business concept based on internal factors (inside) and external factors (outside) Namely strengths, weaknesses, opportunities and threats, Analysis used to compile the factors of the company's strategy, as a result of handicrafts, radha wood carving art is very influential on the supporting community both in interacting and communicating, because this craft takes the form of a variety of letters, names and so forth. wood crafts are also often viewed as home decorations and key chains that are unique and attract attention for teenagers and children. product excellence and good service to customers, so the opportunity creates customer loyalty to the product. Radha wood carvings also always try to make new design innovations so that customers remain interested and provide comfort to their customers. The obstacles facing the Radha wood carving are capital problems, scarcity of raw materials and competition from within the country.